Variasi Dialek Bahasa Jawa Ngoko, Krama dan Krama Inggil di Daerah Oku Timur (Kajian Dialektologi) - Agustin, Shelly Retno; Armariena, Dian Nuzulia; Hetilaniar, Hetilaniar (Indonesian Research Journal on Education, 2023)
This research is motivated by the diversity of language in a community group in the East Oku area which is dominated by the Javanese language. This research aims to describe the lexical differences of Javanese dialect variations and also describe and illustrate the mapping of Javanese dialect variations. The problems revealed in the research regarding the variation of Javanese dialect ngoko, krama, and krama inggil in the East Oku area (dialectological study). The source of informants of this research is the community or people who are elders in the village and understand the Javanese language Krama Ingil aswell as native Javanese people who migrated to Karang Binangun II Village. The research method is descriptive qualitative, with data collection techniques using interviews, recording, and simak libat cakap techniques. Data analysis was carried out using the intralingual pairing technique that connects lingual elements that refer to the meaning of the elements in the language. The results of the study can be concluded that dialectal variation is a diversity of languages that have relationships and differences in language use as well as the meaning caused. Phonological variation, experiencing changes in vowels /a/,/i/, /u/, /e/, /o/. Lexical variation is determined by the same meaning in different languages. Whilegrammatical variation is influenced by affixation, repetition, or fusion, in two regions that cause changes in meaning.